Current State of Business Development in Kazakhstan - KIRDASINOVA, K. A.; MUFTIGALIEVA, A. A.; ZHANSEITOVA, G. S.; DEMESSINOV, T. Zh.; KURMANOV, N. A.; BAITENOVA, L. M.; SELEZNEVA, I.V. (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
Development of small and medium-sized enterprises is one of the conditions for successful economic reform. The creation and development of small and medium-sized businesses is the basis for the social restructuring of society, providing training of the population and the transition of the entire economy to a market economy. In this regard, this article reviewed and due to the potential of small and medium-sized enterprises as a driving force for the formation and development of the market. This article deals with the problems of development of business in the Republic of Kazakhstan. We analysed the characteristics and functioning of the legitimate conditions of small and medium-sized businesses in the country and regional level. The article identified and the necessity of state support of entrepreneurship. On the basis of the study the authors propose an algorithm for a regional assessment and the effectiveness of business operations. Based on the theoretical analysis of the problems of economic development of countries with economies in transition recommendations on adaptation in Kazakhstan, the theory and practice of formation of business management systems.